Climate and land-use change impacts on potential solar photovoltaic power generation in the Black Sea region. Issue 46 (February 2015) - Gunderson, I.; Goyette, S.; Gago-Silva, A.; Quiquerez, L.; Lehmann, A.
Highlights: The solar resource is sufficient to provide PV power at suitable locations within the Black Sea catchment. Climate change will not significantly impact the solar resource, although uncertainty exists. Land-use change will significantly impact potential PV power, although socio-economic factors will have more importance. It is important to strengthen regional cooperation for the integration of renewable energy resources. Abstract: Climate change is a naturally occurring phenomenon that has recently been greatly impacted by anthropogenic greenhouse gas (GHG) emissions. One of the main contributing sectors to GHG emissions is the energy sector, due to its high dependency on fossil fuels. Renewable energy systems, notably solar energy, can be an effective climate change mitigation alternative. Photovoltaic (PV) technology provides an interesting method to produce electricity through a virtually infinite renewable resource at the human time scale: solar radiation. This study evaluates the current and future solar energy potential through the use of grid-connected PV power plants at the scale of countries within the Black Sea catchment. Simulated data are used to determine potential change in climate and land-use according to two different development scenarios. Incident solar radiation flux from re-analyses, spatial interpolation, and the application of the Delta change method are used to assess the current and future solar resource potential within this catchment. Potential sites suitable for PV power plants are selected following a Fuzzy logic approach, and thus the total potential solar energy through PV power generation can be determined. Results show that climate change will have little impact on the solar radiation resource, while land-use change induces more variability. However, regardless of the scenario followed, the solar energy potential is sufficient to provide an interesting contribution to the electricity generation mix of most countries within the Black Sea region.